2019
DOI: 10.1093/mnras/stz2218
|View full text |Cite
|
Sign up to set email alerts
|

SDSS-IV MaNGA: environmental dependence of gas metallicity gradients in local star-forming galaxies

Abstract: Within the standard model of hierarchical galaxy formation in a ΛCDM Universe, the environment of galaxies is expected to play a key role in driving galaxy formation and evolution. In this paper we investigate whether and how the gas metallicity and the star formation surface density (Σ SFR ) depend on galaxy environment. To this end we analyse a sample of 1162 local, star-forming galaxies from the galaxy survey Mapping Nearby Galaxies at APO (MaNGA). Generally, both parameters do not show any significant depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 87 publications
3
13
0
Order By: Relevance
“…While we lack representative samples for which both resolved HI and SFR maps are available, the advent of large optical IFS surveys is gradually providing us with important insights on how group environment affects the SFR surface density profiles of satellites. Intriguingly, while pretty much all studies so far (e.g., Schaefer et al 2017Schaefer et al , 2019aMedling et al 2018;Lian et al 2019;Spindler et al 2018;Coenda et al 2019;Bluck et al 2020 but see also Eigenthaler et al 2015 for a narrowband-based approach) suggest that the SFR density distribution in group satellites is significantly less affected by environment than observed in nearby clusters, the agreement between these works stops here. Schaefer et al (2017) take advantage of the Sydney-AAO Multi-Object Integral-Field Spectrograph (SAMI) Galaxy Survey (Bryant et al 2015) to show that the Hα SFR profiles of galaxies (with no distinction between centrals and satellites) become steeper with increasing environmental density at fixed stellar mass, consistently with what is expected if star formation is quenched outside-in.…”
Section: Sfr Surface Density Profilesmentioning
confidence: 51%
“…While we lack representative samples for which both resolved HI and SFR maps are available, the advent of large optical IFS surveys is gradually providing us with important insights on how group environment affects the SFR surface density profiles of satellites. Intriguingly, while pretty much all studies so far (e.g., Schaefer et al 2017Schaefer et al , 2019aMedling et al 2018;Lian et al 2019;Spindler et al 2018;Coenda et al 2019;Bluck et al 2020 but see also Eigenthaler et al 2015 for a narrowband-based approach) suggest that the SFR density distribution in group satellites is significantly less affected by environment than observed in nearby clusters, the agreement between these works stops here. Schaefer et al (2017) take advantage of the Sydney-AAO Multi-Object Integral-Field Spectrograph (SAMI) Galaxy Survey (Bryant et al 2015) to show that the Hα SFR profiles of galaxies (with no distinction between centrals and satellites) become steeper with increasing environmental density at fixed stellar mass, consistently with what is expected if star formation is quenched outside-in.…”
Section: Sfr Surface Density Profilesmentioning
confidence: 51%
“…This point is made in Section 4.3, where we rule out starvation as the primary driver of the environmental effects discussed in this work. Additionally, we note that Lian et al (2019) placed no constraints on the inclination of galaxies in their sample to the line of sight. This may explain the differences in the metallicity gradients from those reported in our work.…”
Section: Other Studies Of the Environmental Dependence Of Metallicitymentioning
confidence: 94%
“…In a recent study, Lian et al (2019) used MaNGA data to study the metallicity gradients of galaxies as a function of the local environmental overdensity. They found that the metallicity gradients in low-mass satellite galaxies are shallower in dense environments, with a higher metallicity in their outer parts than similar galaxies in the field.…”
Section: Other Studies Of the Environmental Dependence Of Metallicitymentioning
confidence: 99%
“…Furthermore, both Peng & Maiolino (2014a) and Lian et al (2019) find that the environmental dependence (in terms of the local overdensity) of the gas-phase metallicities of star-forming satellites decreases with increasing stellar mass. Again, while we do not see this trend in the stellar metallicities of star-forming satellites, it is readily apparent for passive satellites.…”
Section: Appendix C: Comparison With Gas-phase Metallicity Studiesmentioning
confidence: 99%